Entrepreneurial Motivation Through Creative Economy for Assisted Residents - Sugito, Sugito; Fauziah, Puji Yanti; Tristanti, Tristanti; Kusumawardani, Erma; Santi, Fitta Ummaya; Dewi, Adin Ariyanti (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan Universitas Negeri Semarang, 2021)
Community behavior becomes one thing that affects the imbalance of life because of the emergence of several behaviors that are considered deviant. So that thebarometer of people's behavior cannot be separated from the norms and values inthat society. Nowadays, the correctional facility is still seen as a place / place thatis solely for giving punishment to people who are considered to have committedacts of social deviation. However, the goal of correctional facilities is a correctionalsystem held in order to form prisoners to become fully human, aware of mistakes,improve themselves and not repeat criminal acts so that they can be accepted againin the community. So that this research, which is conducted through participatoryaction research, is focused on increasing the empowerment of assisted residents inprisons which are developed based on the concept of empowerment. Activitiesassociated with current needs are more directed at the creative industry. Thedecoupage training activity carried out as a form of action goes according to plan.And it can provide benefits in increasing knowledge and skills as well asmotivation in entrepreneurship of the assisted residents so that they can becomeprovisions for the inmates after completing a period of detention.